PELATIHAN KETRAMPILAN DAN EDUKASI MENJAGA KEBERSIHAN ORGAN REPRODUKSI, PERUBAHAN HORMONAL DAN MOOD MASA MENOPAUSE PADA LANSIA - kustin (LPPM Universitas dr. Soebandi, 2025)
Menopause is a natural phase in a woman's life characterized by the cessation of the menstrual cycle and significant physical and psychological changes due to a decrease in estrogen levels. Elderly women entering this stage often experience mood disorders, hormonal changes, and issues related to reproductive organ hygiene, which can affect their quality of life. This community service activity aimed to provide skills training and education to elderly women on the importance of maintaining reproductive hygiene, as well as understanding hormonal and psychological changes during menopause. The implementation methods included health education sessions, interactive discussions, and practical simulations on personal hygiene, conducted within the elderly community environment. The results showed an increase in participants’ understanding of the topics presented, along with growing awareness and motivation to adopt a healthy lifestyle appropriate for menopausal conditions. The average knowledge score before the training was 60.2 and increased to 85.6 after the training. This activity is expected to help elderly women go through menopause in a healthier, more comfortable, and independent manner. This activity had a positive impact in increasing the elderly's understanding and awareness of the importance of maintaining reproductive health and recognizing the physical and psychological changes that occur during menopause. Through a communicative and interactive approach, participants became more open to discussing issues that were previously considered taboo. In addition, the training also helped